PERAN ORANG TUA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SELAMA PANDEMI COVID-19 DI LINGKUNGAN III KECAMATAN SOSORGADONG - Maswaras Hari Hutagalung; Zulfadli Nasution; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2021)
The background of this research is Covid- 19 pandemic that caused feeling boring of students in learning. This case requires the parents to help the students in learning at home and giving motivation so the students to get maximum achievement. The aim of this study is know the role of the parent to improve students’ mathematics motivation in Covid-19 pandemic period in Lingkungan III, Sosorgadong sub-distirct. The approach of the research used qualitative descriptive and subject is all students (SMP) in Lingkungan III, Sosorgadong sub-distirct. Questionnaire and interview were used in collecting the data. the result of the research shows the role of the parents to improve students’ mathematics motivation in Covid-19 pandemic period includes accompanying, controlling, supervising the students in teaching learning, and completing facilities the students.